Looking into the causes and coping strategies of reading anxiety among Indonesian EFL students - Salsabila, Nasywa; Mardiah, Radiatan; Wachyunni, Sri (Journal on English as a Foreign Language, 2026)
While reading anxiety considerably hinders English as a foreign language (EFL) students’ English proficiency, research precisely exploring the causes of reading anxiety and coping strategies in the Indonesian EFL context remains limited. This qualitative case study investigated the experiences of ten purposively selected female undergraduate students at a public university in Jambi,  Indonesia. Data were gathered through a semi-structured interview and a reading stimulus task during the interviews, then analyzed using thematic analysis and validated through member-checking to ensure trustworthiness. Results reveal that participants’ anxiety stems from three primary themes: personal factors, material-related features, and procedural factors. Specific triggers include the fear of making pronunciation mistakes, embarrassment over accents, unfamiliar vocabulary, and pressure from timed reading tasks. To mitigate these challenges, students employ self-relaxation techniques, such as positive self-affirmation and physical relaxation, and self-preparation strategies, including reviewing materials and utilizing digital learning tools. These findings suggest that reading anxiety is a multidimensional issue shaped by both personal insecurities and classroom dynamics. Consequently, educators must play a pivotal role by fostering supportive environments and selecting culturally accessible materials to minimize anxiety triggers, ultimately helping students achieve their learning goals.